An opportunistic approach to deal with real-time mesh communication in wireless sensor networks - Erico Leão (2014)
In this paper we propose a novel approach, named Real-Time Alternative-Route Definition (RT-ARounD), to support real-time message streams over large-scale wireless sensor networks. Starting from a standard cluster-tree topology, where each cluster has active and inactive periods, the proposal selects a set of nodes to build a mesh topology which is used during the inactive periods of the respective clusters to transmit messages with real-time requirements. This new topology is built considering shortest path routes between source and sink nodes. In that way, the number of hops that a real-time message needs to transverse can be drastically reduced, thereby improving the real-time responsiveness of the overall network. Moreover, the use of the inactive period guarantees that the normal cluster-tree operation remains unaffected.